2009
DOI: 10.1111/j.1365-294x.2009.04171.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of biotransformation genes in woodrat (Neotoma) herbivores on novel and ancestral diets: identification of candidate genes responsible for dietary shifts

Abstract: The ability of herbivores to switch diets is thought to be governed by biotransformation enzymes. To identify potential biotransformation enzymes, we conducted a large-scale study on the expression of biotransformation enzymes in herbivorous woodrats (Neotoma lepida). We compared gene expression in a woodrat population from the Great Basin that feeds on the ancestral diet of juniper to one from the Mojave Desert that putatively switched from feeding on juniper to feeding on creosote. Juniper and creosote have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 43 publications
1
72
0
Order By: Relevance
“…One treatment was fed powdered rabbit chow amended with resin from creosote bush; the other group was fed a control diet of the same powdered rabbit chow with no additions. Resin was extracted and creosote diets prepared as in [34]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One treatment was fed powdered rabbit chow amended with resin from creosote bush; the other group was fed a control diet of the same powdered rabbit chow with no additions. Resin was extracted and creosote diets prepared as in [34]. …”
Section: Methodsmentioning
confidence: 99%
“…Comparative data on enzyme activities and gene expression of populations of N. lepida support this contention. Neotoma lepida that feed on juniper have different enzyme activity and gene expression profiles compared to those that feed on creosote even when they are fed the same diet [32-34]. Indeed, populations of N. lepida in the Mojave desert have adapted to a diet of creosote as evidenced by their ability to ingest greater quantities of creosote compared to those from the Great Basin desert that feed on juniper and have no prior exposure to creosote [35].…”
Section: Introductionmentioning
confidence: 99%
“…First, evolution may shape the responses of herbivores to PSMs by producing genetic diVerences between separated populations. Indeed, Magnanou et al (2009) demonstrated diVerences in the expression of biotransformation genes between two populations of woodrats when fed either juniper or creosote bush. Perhaps the best example, in the case of brushtail possums, is the diVering ability of possums in diVerent parts of Australia to metabolise Xuoroacetate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the general concepts of pharmacology were introduced to ecologists to explain plant-herbivore interactions 38 years ago (Freeland and Janzen, 1974), the empirical use of pharmacology to understand mechanisms driving foraging patterns in any system is limited (Haley et al, 2008;Magnanou et al, 2009;Marsh et al, 2006b;McLean and Duncan, 2006;Sotka et al, 2009). In contrast to the broad knowledge base that exists on the mechanisms required to process nutrients as well as mechanisms used by domestic and laboratory species to metabolize drugs, there is a general lack of understanding of how PSMs are processed by herbivores, especially in the context of a variable nutrient environment (Appel, 1993;Casarett et al, 2008;Gross and Bakker, 2012;Karasov and Hume, 1997).…”
Section: Pharmacological Mechanismsmentioning
confidence: 99%